A complementary fusion-based multimodal non-destructive testing and evaluation using phased-array ultrasonic and pulsed thermography on a composite structure - Torbali, Muhammet E.; Zolotas, Argyrios; Avdelidis, Nicolas P.; Alhammad, Muflih; Ibarra-Castanedo, Clemente; Maldague, Xavier P. (MDPI, 2024)
Combinative methodologies have the potential to address the drawbacks of unimodal non-destructive testing and evaluation (NDT & E) when inspecting multilayer structures. The aim of this study is to investigate the integration of information gathered via phased-array ultrasonic testing (PAUT) and pulsed thermography (PT), addressing the challenges posed by surface-level anomalies in PAUT and the limited deep penetration in PT. A center-of-mass-based registration method was proposed to align shapeless inspection results in consecutive insertions. Subsequently, the aligned inspection images were merged using complementary techniques, including maximum, weighted-averaging, depth-driven combination (DDC), and wavelet decomposition. The results indicated that although individual inspections may have lower mean absolute error (MAE) ratings than fused images, the use of complementary fusion improved defect identification in the total number of detections across numerous layers of the structure. Detection errors are analyzed, and a tendency to overestimate defect sizes is revealed with individual inspection methods. This study concludes that complementary fusion provides a more comprehensive understanding of overall defect detection throughout the thickness, highlighting the importance of leveraging multiple modalities for improved inspection outcomes in structural analysis.
Keywords: non-destructive testing; fusion in NDT & E; combinations of NDT & E; multimodal NDT& E; phased-array ultrasonic testing; pulsed thermography; composite structures; 40 Engineering; 34 Chemical sciences